Migración y desempleo: estudio del caso de Colombia a través de un modelo de diferencias en diferencias. (2022)
This research aims to measure the impact of migration from Venezuela on the labor market in Colombia, more specifically on the unemployment rate. For this purpose, a qualitative analysis of the unemployment rate in Colombia and the migratory process between Colombia and Venezuela is carried out, in order to better contextualize the problem. After that, through an econometric model of differences in differences, the impact of migration on unemployment will be measured, using a control group and a treatment group made up of departments of Colombia, in a period of time from 2012 to 2020, with 2016 as the impact date. This research is intended to contribute to the Colombian economic literature on this topic, since the results of different past investigations present different results between them, so there is no fairly accurate answer at the moment. to talk about the effect that Venezuelan migration has on unemployment in Colombia.